JOB SATISFACTION AND EMPLOYEES’ WORK PERFORMANCE: A CASE STUDY OF PEOPLE’S BANK IN JAFFNA PENINSULA, SRI LANKA - Nimalathasan, B. (University of Craiova, Faculty of Economics and Business Administration, 2010)
For the purpose of this study, the data was extracted from the branches of people’s bank operating within Jaffna peninsula, Sri Lanka. Here, we analysed the data by employing simple correlation analysis. In the analysis, it is found that there is a positive relationship between job satisfaction and employees’ work performance. That is high level of fair promotion, reasonable pay system appropriate work itself and good working condition leads to high level of employees’ performance. In other words, employee’s job satisfaction has positive impact on their performance. Moreover, outcome of the research would be helpful to the academicians, practitioners, researchers, planners, and policy makers who are involved in the concerned area
Keywords: job satisfaction employees